2011
DOI: 10.1016/b978-0-12-386495-6.00001-1
|View full text |Cite
|
Sign up to set email alerts
|

Marital Quality and Families of Children with Developmental Disabilities

Abstract: In the current review, we highlight recent research on marital quality in parents of children with developmental disabilities (DD) and discuss the child and family factors that account for why some marriages fare better than others. We will also discuss the need for the field of DD to broaden its perspective on marital quality and to examine the impact of marriages on child well-being and the well-being of parents. The clinical implications of recent research findings on marital quality for improving supports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 99 publications
2
18
0
1
Order By: Relevance
“…[ 14 ] A review article on the marital quality of families having children with developmental disorders including ASD reported that the divorce rates are higher for the families of children with ASD, and more depression, anxiety, and other mental health problems are seen in the parents. [ 15 ] Moreover, it was suggested that the marital quality of the parents affects the development and well-being of the child. [ 16 ] Mothers had a higher number of important support needs that are unmet than fathers, and the educational status of the parents, the age of the child with ASD, accompanying behavioral disorders, the presence of mental retardation, and the level of income are associated with the support needs of the mothers.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] A review article on the marital quality of families having children with developmental disorders including ASD reported that the divorce rates are higher for the families of children with ASD, and more depression, anxiety, and other mental health problems are seen in the parents. [ 15 ] Moreover, it was suggested that the marital quality of the parents affects the development and well-being of the child. [ 16 ] Mothers had a higher number of important support needs that are unmet than fathers, and the educational status of the parents, the age of the child with ASD, accompanying behavioral disorders, the presence of mental retardation, and the level of income are associated with the support needs of the mothers.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no study has examined the marital relationships of parents of individuals with FXS. Findings involving families of children with other developmental disabilities are mixed, suggesting that the presence of a child with a disability may or may not impart risk for poor marital functioning (see Hartley et al 2011 for a review). Examinations of the correlates of marital functioning within families of children with developmental problems have produced somewhat mixed results.…”
Section: Introductionmentioning
confidence: 99%
“…The level of parental stress in such families is significantly higher than the level of stress of parents of children of normative development (Bluth, Roberson, Billen, & Sams, 2013). Children with disabilities are more dependent on their parents than children of normative development; therefore, research on parental stress and protective/risk factors is extremely important for empowering parents for this very important role (Hartley, Mailick Seltzer, Barker & Greenberg, 2011).…”
Section: Parental Stress In the Upbringing Of Children With Normativementioning
confidence: 99%
“…By finding adaptive ways to deal with stress, parents contribute to the adjustment of the whole family. Adaptive ways of coping with stress are associated with the psychological well-being of parents (Hartley, Mailick Seltzer, Barker, & Greenberg, 2011) and, thus, certainly contribute significantly to a positive family climate. However, it is also important to point out that family functioning is significantly affected by the child's disability.…”
Section: The Close Relationships Of Parents With Children Of Normativmentioning
confidence: 99%